Exploring Junior High School English Teachers' Pedagogical Knowledge in Solok Regency - Caca Yunisari; Aryuliva Adnan (Universitas Negeri Padang, 2022)
The researcher conducted descriptive qualitative research. The source of data in this research divided into two parts: teachers and documents. the researcher conducted the research in Solok Regency, West Sumatera. the researcher used a purposive or judgmental sampling technique. In purposive or judgmental sampling, the researcher chose this technique based on some criteria, those were the location, school accreditation, experienced teachers, and grade eight. The researcher used two instruments in this research, which were document and observation in gathering the information that the researcher was needed. In detail, the pedagogical knowledge divided into three criteria. Those were preparing the lesson or lesson plan (approach of teaching, methods of teaching, class activity, and assessment), implementing the class activity (classroom management), and evaluation or implementation of assessment. In preparing the lesson, all teachers use the same approach and methods of teaching language. This showed a positive result that they design the lesson plan used pedagogical knowledge without left-behind the 2013 Curriculum instruction. Also, they were able to perform the learning stages with good classroom management and assessment session. However, there are some improvements still needed for the teaching performance due to not all the learning stages well implemented. This case especially happened in the whilst-teaching.